Heritage movements in Asia : cultural heritage activism, politics, and identity - Mozaffari, Ali; Jones, Tod, 1977- (Explorations in heritage studies, 2020)
"Heritage processes vary according to cultural, national, geographical, and historical contexts. This volume is unique in that it is dedicated to approaching the analysis of heritage through the concepts of social movements. Adapting the latest developments in the field of social movements, the chapters examine the formation, use and contestation of heritage by various official, non-official and activist players and the spaces where such ongoing negotiations and contestation take place. By bringing social movements into heritage studies, the book advocates a shift of perspective in understanding heritage, one that is no longer bound by (at times arbitrary) divisions such as those assumed between the state and people or between experts and non-experts"--